Miguel Torga, viajero por España: Testimonios sobre la guerra civil en sus escritos - Navas Sánchez-élez, M.ª Victoria (Revista de Filología Románica, 2006)
This article is the research and analysis of Diário, A Criação do Mundo, Poemas Ibéricos, Bichos, Portugal and Novos Contos da Montanha by Miguel Torga and their testimonies about the Spanish Civil War.